Investigating The Factors Affecting Succession Planning In The Leadership Of Healthcare Organizations In Iran: A Stakeholder Perspective - Saeede Afshari; SHaghayegh Vahdat; Iravan Masoudi asl; Somayeh Hesam (Tehran University of Medical Sciences, 2024)
Background and purpose: In today's competitive organizational landscape, the significance of recruiting and developing competent human resources has become paramount. Organizations not only aim to select and attract capable and efficient personnel but also seek to enhance and expand their capabilities. Consequently, the concept of meritocracy has become a key concern for modern organizations. This study aims to investigate the factors influencing succession planning in the leadership of healthcare organizations in Iran. Methods: This qualitative study was conducted using content analysis in 2020. The statistical population comprised key decision-makers and policymakers in successful and prominent Iranian organizations known for effective succession planning, such as the Islamic Revolutionary Guard Corps (IRGC) and the public banking system. A total of 15 experts were selected through purposive and snowball sampling, with data collection continuing until theoretical saturation was achieved. Data were gathered through structured interviews, and the analysis and coding were performed using MAXQDA 11 software. Results: The study identified five main themes: alignment of strategic goals and needs analysis, strategic communication and organizational structure, talent identification and empowerment, development and excellence of qualified individuals, and monitoring of succession planning programs. These were further divided into 13 sub-themes. Conclusion: Organizations and managers should provide comprehensive support and demonstrate commitment to the effective implementation of succession planning programs. This will lead to improved organizational decisions and policies, ensuring that competent and qualified individuals are placed in key positions. Additionally, this approach will enhance work quality, boost employee motivation, reduce resource wastage, and improve career advancement opportunities for staff.